PENINGKATAN KOMPETENSI GURU PAUD/TK MELALUI PELATIHAN CANVA SEBAGAI INOVASI MEDIA PEMBELAJARAN - Suliswaningsih; Dani Arifudin; Retno Waluyo; Gilang Miftakhul Fahmi; Mohamad Syahri Nurrochim (Nusantara Hasana Journal, 2023)
According to Permendikbud Number 18 of 2018 concerning the Provision of Early Childhood Education Services, it explains that the quality of an PAUD service can be seen from its learning innovation, increasing the capacity of educators and education personnel to innovate learning, as well as the provision of facilities and infrastructure. The problem faced by most educators in PAUD services is the lack of ability to develop innovative learning media, so they tend to use conventional methods such as lectures. Early childhood requires a visual learning method, so that students understand the material presented by the teacher. The ability to create interesting learning media must of course be balanced with mastery of design using computers. This service aims to provide training for PAUD teachers to be able to create innovative learning media using the Canva application. Canva is an application that will help teachers to design easily, even if they don't have graphic design skills. The service is carried out by the lecture method on the explanation of the material, then the participants carry out practical work on making learning media. The result of this activity is that PAUD teachers can improve competence through training in making learning media using the Canva application.